Empirical cefepime+vancomycin versus ceftazidime+vancomycin versus meropenem+vancomycin in the treatment of healthcare-associated meningitis: results of the multicenter ephesus study - TİGEN, ELİF (My University, 2023)
BACKGROUND: Herein, we analyzed the efficacy of main antibiotic therapy regimens in the treatment of healthcare-associated meningitis (HCAM). MATERIALS/METHODS: This retrospective cohort study was conducted in 18 tertiary-care academic hospitals Turkey, India, Egypt and Romania. We extracted data and outcomes of all patients with post-neurosurgical meningitis cases fulfilling the study inclusion criteria and treated with empirical therapy between December 2006-September 2018. RESULTS: Twenty patients in the cefepime + vancomycin-(CV) group, 31 patients in the ceftazidime + vancomycin-(CFV) group, and 119 patients in the meropenem + vancomycin-(MV) group met the inclusion criteria. The MV subgroup had a significantly higher mean Glasgow Coma Score, a higher rate of admission to the intensive care unit within the previous month, and a higher rate of antibiot herapy within the previous month before the meningitis episode (p 0.05) among the three cohorts. No regimen was effective against carbapenem-resistant bacteria, and vancomycin resulted in an EOT clinical success rate of 60.6% in the methicillin-resistant staphylococci or ampicillin-resistant enterococci subgroup (n = 34). CONCLUSIONS: Our study showed no significant difference in terms of clinical success and mortality among the three treatment options. All regimens were ineffective against carbapenem-resistant bacteria. Vancomycin was unsuccessful in approximately 40% of cases involving methicillin-resistant staphylococci or ampicillin-resistant enterococci.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; BULAŞICI HASTALIKLAR; Life Sciences (LIFE); IMMUNOLOGY; INFECTIOUS DISEASES; Bulaşıcı hastalıklar; Sağlık Bilimleri; Infectious Diseases; Health Sciences; Antibiotics; Empirical therapy; Glycopeptides; Healthcare-associated meningitis; Multicenter study